A normative analysis of the South African laws, regulations and professional guidelines regarding human embryonic stem cell research and therapies - Mnisi, Fikile Muriel (My University, 2018)
Human Embryonic Stem Cell (hESC), like any other Biotechnology comes, not only with the potential to advance scientific knowledge and therapeutic development, but also with ethical controversies. These controversies not only affect scientific growth but also how the technology will be governed through policies and the legal framework. This study normatively analyzes the effect that the South African laws, regulations and professional guidelines have on hESC research and therapies. Three theoretical ethical approaches are applied in order to normatively analyze the legal regime, namely: Ubuntu, Ethics of Responsibility and Social Contract. The study argues that the legal framework is not clear and lacks coherence in how hESC research and therapies are regulated. Based on the findings, I propose an ethical policy framework for hESC research and therapies that may ensure flexibility and facilitation of growth and development for hESC technologies within South Africa and Africa.
A Thesis submitted to the Faculty of Health Science, University of the Witswatersrand, in fulfillment of the degree of Doctor of Philosophy,Johannesburg, 2018